PETN-Induced Antioxidative Properties in Endothelial Cells as a Target for Secondary Prevention of Endothelial Dysfunction in Pregnancy - Teichert, Veronika; Große, Silke; Multhaup, Anna; Müller, Jasmin; Gutierrez-Samudio, Ruby N.; Morales-Prieto, Diana M.; Groten, Tanja (Frontiers in Physiology, 2022)
The NO-donor Pentaerytrithyltetranitrate (PETN) has vasodilatative properties and direct protective effects on endothelial cells. We formerly demonstrated that PETN, given to pregnant women during the second and third trimester, influences endothelial dysfunction related pregnancy complications like preeclampsia (PE) and fetal growth restriction (FGR). PETN treatment showed to delay PE to late pregnancy and achieved a profound risk reduction for FGR and/or perinatal death of 40%. The aim of this study was to confirm the effect of PETN on endothelial cell dysfunction at molecular level in an experimental approach. To induce endothelial dysfunction HUVEC were treated with 10 U/l of thrombin in the presence or absence of PETN. qRT-PCR analysis showed that PETN induced the expression of heme-oxygenase-1 and superoxide dismutase 2 but not endothelial NO-synthase under basal conditions. The induction of antioxidant proteins did not change basal reactive oxygen species (ROS) levels as measured by MitoSOX™ staining. PETN treatment significantly delayed the thrombin-induced disruption of the endothelial monolayer, determined using the xCELLigence® and attenuated the disrupting effect of thrombin on tubular junctions as seen in a tube-forming assay on Matrigel™. In western-blot-analysis we could show that PETN significantly reduced thrombin-induced extracellular signal-regulated kinase activation which correlates with reduction of thrombin-induced ROS. These experimental results establish the concept of how PETN treatment could stabilize endothelial resistance and angiogenic properties in pregnancy-induced stress. Thus, our results underscore the assumption, that the shown clinical effects of PETN are associated to its endothelial cell protection.